PENGARUH PERILAKU APARATUR TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR CAMAT BUNTA KABUPATEN BANGGAI - Rahmad, Rahmad (Katalogis, 2014)
The Influence of Apparatus’ Behaviour to Service Quality at Bunta District BanggaiRegency). This research was aimed to study and analyze : 1) the apparatus’ behaviour to service quality at Bunta Sub-district; 2) the dominant factors that influence the apparatus’ behavior to service quality at Bunta at Sub-district. Adopted fromthe theory Siagian S.P and Ndraha T. The population of this study the sub district apparatus, Sub-village, Village, and all communities involved 2.369 people. Sample was drawn through purposive sampling. The sample of this research was gathered from 3 group communities; 3 (three) villages and 1 (one) Sub-village located at Bunta district consisted 50 people and the head of Sub-village, head of Village, and staff of district of Bunta as respondent. The data collection was conducted through observation, questionnaire , interview, and documentation, while the data was analysis through quantitative, frequently table and percentage table. The study result shows that the service quality of Apparatus of district Bunta Banggai Regency still not good.